The Spiral Structure in the Solar Neighborhood - Hou, L. G. (Frontiers in Astronomy and Space Sciences, 2021)
The spiral structure in the Solar neighborhood is an important issue in astronomy. In the past few years, there is significant progress in observation. The distances for a large number of good spiral tracers, i.e. giant molecular clouds, high-mass star-formation region masers, $\hii$ regions, O-type stars and young open clusters, have been accurately estimated, making it possible to depict the detailed properties of nearby spiral arms. In this work, we first give an overview about the research status for the Galaxy's spiral structure based on different types of tracers. Then the objects with distance uncertainties better than 15% and $<$0.5~kpc are collected and combined together to depict the spiral structure in the Solar neighborhood. Five segments related with the Perseus, Local, Sagittarius-Carina, Scutum-Centaurus and Norma Arms are traced. With the large dataset, the parameters of the nearby arm segments are fitted and updated. Besides the dominant spiral arms, some substructures probably related to arm spurs or feathers are also noticed and discussed.